Domed roof of the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
The Vyankatesh Balaji Temple has an amalgamation of various styles that were popular in the Deccan during the eighteenth century. For example, the domed roof, use of multi-foil arches, double-layered foliated band running around the exterior of the dome, are typical of Islamic architecture. On the other hand, the use of the Mangalore-tiled hip roof, wooden sabha mandap, musicians on the domed roof, and deepastambha are elements taken from Hindu temples of the Konkan and Maharashtra regions.